Microwave transmission-line impedance data - Gunston, M. A. R. (Noble Publishing Corp., 1997)
The book reviews developments in the following fields: transmission lines utilizing conductors of circular cross-section; transmission lines utilizing conductors of rectangular cross-section; transmission lines utilizing conductors of both circular and rectangular cross-section; transmission lines of 'unusual' cross-section; and coupled transmission lines.